2020
DOI: 10.5194/tc-14-2283-2020
|View full text |Cite
|
Sign up to set email alerts
|

Results of the third Marine Ice Sheet Model Intercomparison Project (MISMIP+)

Abstract: Abstract. We present the result of the third Marine Ice Sheet Model Intercomparison Project, MISMIP+. MISMIP+ is intended to be a benchmark for ice-flow models which include fast sliding marine ice streams and floating ice shelves and in particular a treatment of viscous stress that is sufficient to model buttressing, where upstream ice flow is restrained by a downstream ice shelf. A set of idealized experiments first tests that models are able to maintain a steady state with the grounding line located on a re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 56 publications
3
91
1
Order By: Relevance
“…Results from an idealized case comparing coupled ice-ocean models with different melt parameterizations suggested that a nonlocal, quadratic melt parameterization was best able to mimic the coupled ice-ocean results over a broad range of ocean forcing (Favier et al, 2019). These results were performed on an idealized case similar to the Marine Ice Sheet Ocean Model Intercomparison Project (MISOMIP, Asay-Davis et al, 2016;Cornford et al, 2020) and have not yet been tested on realistic geometries. The non-quadratic melt parameterization suggested in Favier et al (2019) is as follows:…”
Section: Oceanic Forcingmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from an idealized case comparing coupled ice-ocean models with different melt parameterizations suggested that a nonlocal, quadratic melt parameterization was best able to mimic the coupled ice-ocean results over a broad range of ocean forcing (Favier et al, 2019). These results were performed on an idealized case similar to the Marine Ice Sheet Ocean Model Intercomparison Project (MISOMIP, Asay-Davis et al, 2016;Cornford et al, 2020) and have not yet been tested on realistic geometries. The non-quadratic melt parameterization suggested in Favier et al (2019) is as follows:…”
Section: Oceanic Forcingmentioning
confidence: 99%
“…Other mechanisms, such as ocean surface waves, rheological weakening, surface load shifts due to water movement or basal melting (MacAyeal et al, 2003;Braun and Humbert, 2009;Borstad et al, 2012;Banwell et al, 2013;Banwell and Macayeal, 2015), have also been proposed to explain these ice shelf collapse but are not investigated in this study. Ice shelf collapse reduces the buttressing forces provided to the upstream grounded ice and leads to acceleration and increased mass loss of the glaciers feeding them (De Angelis and Skvarca, 2003;Rignot et al, 2004), but more dramatic consequences have been envisioned if ice shelves were to collapse in front of thick glaciers resting on retrograde bed slopes (Bassis and Walker, 2011;DeConto and Pollard, 2016). As the presence of liquid water at the surface of Antarctic ice shelves is expected to increase in a warming climate (Mercer, 1978;Trusel et al, 2015), we propose experiments that include ice shelf collapse.…”
Section: Ice Shelf Collapse Forcingmentioning
confidence: 99%
“…This and the fact that ice sheets generally thicken inland lead to a geomet-ric configuration prone to instability; a small increase in flux at the grounding line thins the ice there, leading to floatation, a retreat of the grounding line into deeper water, further increases in flux (due to still thicker ice), and further thinning and grounding-line retreat. This theoretical "marine ice sheet instability" (MISI) mechanism (Mercer, 1978;Schoof, 2007) is supported by idealized (e.g., Schoof, 2007;Cornford et al, 2020) and realistic (e.g., Cornford et al, 2015;Royston and Gudmundsson, 2016) ice sheet modeling experiments, and some studies (Joughin et al, 2014;Rignot et al, 2014) argue that such an instability is currently under way for outlet glaciers of Antarctica's Amundsen Sea Embayment. The relevant perturbation for grounding-line retreat in the Amundsen Sea Embayment is thought to be intrusions of relatively warm, intermediate-depth ocean waters onto the continental shelves, which have reduced the thickness and extent of marginal ice shelves via increased subice-shelf melting (e.g., Jenkins et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…To test the modifications in real-world scenarios at larger scales than the idealized fjord experiments above, we simulate retreat of the West Antarctic ice sheet due to future climate warming. The climate forcing follows that in DeConto and Pollard (2016) for the extreme RCP8.5 greenhousegas emissions scenario, with atmospheric temperatures and precipitation from regional climate model simulations and oceanic temperatures from a transient future simulation with the National Center for Atmospheric Research (NCAR) Community Climate System Model version 4 (CCSM4) global climate model (Shields et al, 2016). The ice sheet is initialized to modern observed (Fretwell et al, 2013) and run from 1950 CE for 500 years.…”
Section: Results: West Antarctic Simulationsmentioning
confidence: 99%
“…In ice-sheet models with two horizontal dimensions, such formulations can be used to prescribe the approximate flow across grounding lines. In our previous work (Pollard and DeConto, 2012;DeConto and Pollard, 2016), this was done simply by applying the 1-D expressions at individual one-grid-cell-wide segments separating pairs of grounded and floating cells, so that the orientation of each single-cell "grounding-line" segment is parallel to either the x or the y axis. Although this is consistent with the one-dimensional character of the formulation in Schoof (2007), it does not capture the actual orientation of the wider-scale grounding line.…”
Section: Introductionmentioning
confidence: 99%